Strategi yang tepat dalam Pengendalian Hama Lalat Buah (Bactrocera sp.) pada Tanaman Jambu Air Hijau Deli (Syzygium aqueum) - Cindi Azzahra; Mutiara Raihanah; Zahratul Fauziah; Meirizqi NS; Azzahra Nur DL; Rohima Rahmah; Chandra Irsan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Azzahra C, Raihanah M, Fauziah Z, NS Meirizqi, DL Azzahra Nur, Rahmah R, Irsan C. 2021. Strategi yang tepat dalam Pengendalian Hama Lalat Buah (Bactrocera sp.) pada Tanaman Jambu Air Hijau Deli (Syzygium aqueum). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 242-248. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Deli green water guava (Syzygium aqeum) is one of the agricultural products in Indonesia that has high economic value. Many pests, are pests for this plant, one of which is fruitfly. Fruitfly (Bactrocera sp.) have 400 species with different levels of attack in each species. Cultivation of this green water guava fruit is very profitable for farmers and can improve their economy. Fruit farmers generally still depend on synthetic pesticides to control fruitfly, even though this method can pollute the environment and the resulting plant products. This review aimed to identify and overcome fruit fly pests that attacked deli green guava with proper control and attention to all aspects. This writing is based on a study of the literature taken and then analyzed and developed into a review that is easy to understand. Fruit fly pest control is usually done by wrapping fruit using plastic. However, farmers are often reluctant to use this method because of the large number of fruits to pack. Another more effective way is to use vegetable insecticide control by using methyl eugenol. It was concluded that the fruit fly pest attack can damage the quality of the green water guava fruit which has an impact on the selling value, so effective control must be used such as the use of methyl eugenol.